Potential selection of antimony and methotrexate cross-resistance in Leishmania infantum circulating strains. - Lorena Bernardo; Ana Victoria Ibarra-Meneses; Noelie Douanne; Audrey Corbeil; Jose Carlos Solana; Francis Beaudry; Eugenia Carrillo; Javier Moreno; Christopher Fernandez-Prada (Public Library of Science (PLoS), 2024)
Background Visceral leishmaniasis (VL) resolution depends on a wide range of factors, including the instauration of an effective treatment coupled to a functional host immune system. Patients with a depressed immune system, like the ones receiving methotrexate (MTX), are at higher risk of developing VL and refusing antileishmanial drugs. Moreover, the alarmingly growing levels of antimicrobial resistance, especially in endemic areas, contribute to the increasing the burden of this complex zoonotic disease. Principal findings To understand the potential links between immunosuppressants and antileishmanial drugs, we have studied the interaction of antimony (Sb) and MTX in a Leishmania infantum reference strain (LiWT) and in two L. infantum clinical strains (LiFS-A and LiFS-B) naturally circulating in non-treated VL dogs in Spain. The LiFS-A strain was isolated before Sb treatment in a case that responded positively to the treatment, while the LiFS-B strain was recovered from a dog before Sb treatment, with the dog later relapsing after the treatment. Our results show that, exposure to Sb or MTX leads to an increase in the production of reactive oxygen species (ROS) in LiWT which correlates with a sensitive phenotype against both drugs in promastigotes and intracellular amastigotes. LiFS-A was sensitive against Sb but resistant against MTX, displaying high levels of protection against ROS when exposed to MTX. LiFS-B was resistant to both drugs. Evaluation of the melting proteomes of the two LiFS, in the presence and absence of Sb and MTX, showed a differential enrichment of direct and indirect targets for both drugs, including common and unique pathways. Conclusion Our results show the potential selection of Sb-MTX cross-resistant parasites in the field, pointing to the possibility to undermine antileishmanial treatment of those patients being treated with immunosuppressant drugs in Leishmania endemic areas.